Correlational Study of Arm Muscle Strength with Long Service Performance in Badminton Athletes - Rusli, Muhammad; Jud; Marsuna (Universitas PGRI Palembang, 2025)
Long serve is one of the basic techniques in badminton that plays an important role in building a game strategy, especially in singles. The ability to perform a consistent and accurate long serve can be a competitive advantage for an athlete. However, the quality of the serve is not only determined by technique, but also by physical factors. This study aims to determine the Correlational Study of arm muscle strength with long serve performance in badminton athletes. This type of research is descriptive using a correlational research method. The population of this study was 40 badminton club athletes from Kendari City. The sampling technique was based on purposive sampling, namely the criteria of male gender, age 15-17 years and being able to do long serves, so that the sample numbered 20 people. The research instruments were push-up tests and long serve ability tests. Based on the correlation test analysis, the relationship between the arm muscle power variable coefficient and the upper serve ability was obtained, where the calculated r value was 0.565 at a significance level of 0.008 <0.05 with a determination coefficient of 0.319 or 31.9%. This means that there is a significant relationship between arm muscle strength and long badminton service ability. The contribution of arm muscle strength to long service ability is 31.9% while 68.1% is influenced by other factors. The study concluded that arm muscle strength has a significant relationship with long service performance in badminton athletes.